PERSONAL QUALITIES IMPORTANT FOR THE PROFESSIONAL ACTIVITY OF THE MODERN MIDDLE LEVEL MANAGER - Khachatryan, Ani (Modern Psychology, 2024)
The peculiarity of this level of management lies in the fact that the middle level manager is the organizer and supervisor of the process of implementation of decisions and actions taken by high-level managers. The modern management system, along with rapid changes in socio-economic conditions, also makes special demands on the middle level manager. In the conditions of modern imperatives, the focus of attention is on the issue of matching the characteristics of managerial activity and the psychological qualities of the manager, which can be the basis for effective activity and professional development. The professional development of middle-level managers is determined by a unique combination of important professional psychological qualities, namely: emotional intelligence, thinking, voluntary self-regulation, social-communication knowledge. The conducted research works provide an opportunity to state that conscientiousness, self-regulation of behavior, and creativity are important personal qualities for a modern middle level manager. Creativity is also characteristic of middle level managers: it is above average among middle level managers. It means that we can talk about such important professional qualities of a modern middle level manager as conscientiousness, control of behavior and creativity.